Interpersonal Communication, Social Criticism, and the Poetic Code in Branko Čegec’s Poetry - BRKIĆ, Beatriz; Rem, Paula (Anafora, 2023)
The aim of this article is to decode the aspects of interpretative categories of interpersonal communication, social criticism, and the poetic code in Branko Čegec’s poetry and prose texts within the poetry collections Uspon i pad Koševskog brda, Sarajevo za prolaznike, and Pun mjesec u Istanbulu, as well as to contribute to the analysis and description of the poetics of his poetry. Čegec’s poems are interpreted with the help of Zoran Kravar’s concept of textual structures of the poetic sign and Jakobson’s and Buhler’s linguistic function, which analyses the internal semantics of the text, while the interpretive analytical system is taken from Goran Rem’s Koreografija teksta and Josip Užarević’s Kompozicija lirske pjesme. The analysis of the phenomenon of interpersonal communication is based on Kathleen Kelley Reardon’s and Roland Burkart’s research. This article analyses the models of diachronic intertextuality within the interpretative category of interpersonal communication, based on ironizing the Petrarchan love code, the function of the subject’s sexuality as a figure of provocation, the process of identity formation through the female subject’s liberation, and time and space categories that create the subject’s inner world. The process of deconstruction and construction becomes a means for creating the subject’s identity or the poetic code of its artistic identity. Intermediality, as one of the main characteristics of Čegec’s poetics and the modern poetics in general, is recognized as a means of social criticism aimed at the limits of art, authority, power, and culture.